Cytomegalovirus infections and anti-GM2 antibodies in Guillain-Barré syndrome. Issue 6 (June 1997) - Jacobs, B C; van Doorn, P A; Groeneveld, J H; Tio-Gillen, A P; van der Meché, F G
Abstract : To investigate whether antecedent cytomegalovirus (CMV) infections in patients with Guillain-Barré syndrome are associated with the presence of specific antiganglioside antibodies, acute phase serum samples from 130 patients with Guillain-Barré syndrome and 200 controls were tested. Anti-GM2 IgM antibodies were found more often in patients with Guillain-Barré syndrome with CMV infection (22%) than in patients without the infection (2%) (P = 0.003). CMV infections may elicit anti-GM2 antibodies in susceptible patients, which may contribute to the pathogenesis of Guillain-Barré syndrome associated with CMV.